(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2017)
Laminar counter and parallel flows in a double pipe heat exchanger is studied experimentally using two types of nanofluids as a cooling medium. The nanofluids consist of Al2O3 and TiO2 nanoparticles, which were added to the base fluid (deionized water). The average diameter of nanoparticles is approximately 20 nm for both Al2O3 and TiO2 nanoparticles. The volume concentrations of nanofluid was varied with a range of (0.05-0.3) percentage and the flow rates of the base and nanofluids were varied with a range of (0.5-2) L/min. Hot fluid (water) is flowing in the inner tube of heat exchanger with constant inlet temperature and the cold fluid (nanofluid) is introduced in the outer tube with constant inlet temperature.Compared to the base fluid, the results showed that the nanofluid containing Al2O3 and TiO2 nanoparticle exhibits enhanced heat transfer, and this enhancing is clearly reflected by the increase in the inside and outside heat transfer coefficients, thus the overall heat transfer coefficient, where the percentage enhancement in heat transfer coefficient of nanofluid per base fluid is (18.25 and 15.5) % for Al2O3-water and TiO2-water nanofluid respectively. The enhanced performance of heat exchanger is due to high value of thermo physical properties of fluid when dispersing nanoparticles in the base fluid.